Greenland and the raven's gift [book review] - Chitrapu, Devi (2002)
Dupre, Kelly. The Raven’s Gift: A True Story from Greenland. Houghton Mifflin, 2001. ISBN 06180011714. $15.00. 32 pp. A 3-6 PB NF Reviewed by Devi Chitrapu This autobiographical story is based on the author’s tour of Greenland. It describes her long journey to the earth’s largest island with all of its magic and mystery. Dupre writes of exploring Greenland’s shores by kayak, visiting tiny villages, and a significant encounter with a raven in its homeland. The book provides readers with useful information about Greenland’s tribal people, particularly the Inuit, describing their source of livelihood, eating habits, survival skills, and popular stories and legends. It also describes the artic animals and birds living in this harsh climate. Many superstitions dominate the lives of the people of Greenland. They believe that the Northern Lights are the spirits of their ancestors playing ball in the sky. Similarly, they believe the raven is a messenger, creator, and even a trickster. Dupre encounters a raven, which gives her a stone and believes that it is sending her a message to find strength and spirit in herself, the land, and the sea. While it does lack a story line, this book has great informative value, which is greatly enhanced by the charming linoleum block prints. It will attract anyone curious about the kind of life that exists in far off places. 32 p. Children's Book and Play Review, June 2002